Topological defect lasers. (1st December 2015) - Knitter, Sebastian; Liew, Seng Fatt; Xiong, Wen; Guy, Mikhael I; Solomon, Glenn S; Cao, Hui
Abstract: We introduce a topological defect to a regular photonic crystal defect cavity with anisotropic unit cell. Spatially localized resonances are formed and have high quality factor. Unlike the regular photonic crystal defect states, the localized resonances in the topological defect structures support powerflow vortices. Experimentally we realize lasing in the topological defect cavities with optical pumping. This work shows that the spatially inhomogeneous variation of the unit cell orientation adds another degree of freedom to the control of lasing modes, enabling the manipulation of the field pattern and energy flow landscape.